2006
DOI: 10.2223/jped.1478
|View full text |Cite
|
Sign up to set email alerts
|

Serum prevalence of celiac disease in children and adolescents with type 1 diabetes mellitus

Abstract: The seroprevalence of celiac disease found in diabetic children and adolescents in Pernambuco is elevated, being comparable with levels observed in studies in North America and Europe and lower than in Africa, suggesting that serological screening for celiac disease should be performed for all children and adolescents with type 1 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
2
14
0
4
Order By: Relevance
“…Patients with positive anti-TTG and normal intestinal biopsy in our study had a low positive anti-TTG level (20–67.8 U/ml) compared with the other 11 patients with higher anti-TTG and proven atrophic mucosa. The low sensitivity and specificity of low positive anti-TTG values for diagnosis of CD have also been observed in other studies [14,15,27]. Another finding that has also been observed by others [16], is that children with T1D, like other autoimmune diseases at risk of CD, could have transiently positive anti-TTG results at low values.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Patients with positive anti-TTG and normal intestinal biopsy in our study had a low positive anti-TTG level (20–67.8 U/ml) compared with the other 11 patients with higher anti-TTG and proven atrophic mucosa. The low sensitivity and specificity of low positive anti-TTG values for diagnosis of CD have also been observed in other studies [14,15,27]. Another finding that has also been observed by others [16], is that children with T1D, like other autoimmune diseases at risk of CD, could have transiently positive anti-TTG results at low values.…”
Section: Discussionsupporting
confidence: 75%
“…The potential for early reversal of abnormalities in indices of intestinal malabsorption (iron and calcium deficiencies) is one of the advantages for screening asymptomatic children for early detection of CD in T1D patients. The predominance of female gender among CD group in the present study has been observed in few studies [25,26], while other studies in different races have shown male predominance [27,28], which likely represents variability of genetic and environmental factors among different races.…”
Section: Discussionsupporting
confidence: 44%
“…The only Brazilian study showing a higher prevalence (15.8%) of biopsy‐proven CD was based in a very small sample (19 patients with T1DM) . The same group carried out another study including 354 T1DM patients and found a prevalence of positive IgA‐tTG of 10.5%, but no information regarding the biopsy‐proven CD was mentioned . Recently, another study, conducted in the northeastern region of Brazil, found a prevalence of positive IgA‐tTG antibodies of 7.4%, but data of the biopsy were not informed as well …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CD in T1DM varies widely. It has ranged from 1.6% to 12.3% in Europe, 17–21 4.8% to 10.5% in South America, 22–23 4.9% to 6.2% in middle East; 24–25 and is highest in North Africa: 21.4% in Libya 26 and 16.4% in Algeria 27 . Among whites in North America, it ranges from 7–8% 14,28 while it is 2.9% among African Americans 29 .…”
Section: Discussionmentioning
confidence: 99%